The SEB-1 transcription factor binds to the STRE motif in Neurospora crassa and regulates a variety of cellular processes including the stress response and reserve carbohydrate metabolism - Freitas, Fernanda Zanolli [UNESP]; Virgilio, Stela [UNESP]; Cupertino, Fernanda Barbosa [UNESP]; Kowbel, David John; Fioramonte, Mariana; Gozzo, Fabio Cesar; Glass, N. Louise; Bertolini, Maria Célia [UNESP] (Oxford University Press (OUP), 2016)
When exposed to stress conditions, all cells induce mechanisms resulting in an attempt to adapt to stress that involve proteins which, once activated, trigger cell responses by modulating specific signaling pathways. In this work, using a combination of pulldown assays and mass spectrometry analyses, we identified the Neurospora crassa SEB-1 transcription factor that binds to the Stress Response Element (STRE) under heat stress. Orthologs of SEB-1 have been functionally characterized in a few filamentous fungi as being involved in stress responses; however, the molecular mechanisms mediated by this transcription factor may not be conserved. Here, we provide evidences for the involvement of N. crassa SEB-1 in multiple cellular processes, including response to heat, as well as osmotic and oxidative stress. The Δseb-1 strain displayed reduced growth under these conditions, and genes encoding stress-responsive proteins were differentially regulated in the Δseb-1 strain grown under the same conditions. In addition, the SEB-1-GFP protein translocated from the cytosol to the nucleus under heat, osmotic, and oxidative stress conditions. SEB-1 also regulates the metabolism of the reserve carbohydrates glycogen and trehalose under heat stress, suggesting an interconnection between metabolism control and this environmental condition. We demonstrated that SEB-1 binds in vivo to the promoters of genes encoding glycogen metabolism enzymes and regulates their expression. A genome-wide transcriptional profile of the Δseb-1 strain under heat stress was determined by RNA-seq, and a broad range of cellular processes was identified that suggests a role for SEB-1 as a protein interconnecting these mechanisms.
Keywords: ChIP-qPCR; Neurospora crassa; RNA-seq; SEB-1; Stress response